THE ADVANTAGES OF THE CANVA APPLICATION IN ENGLISH LEARNING AT HIGH SCHOOL - Sri Nastuti; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The quality of learning depends greatly on the teachers' quality and teaching media materials used especially in English language learning. A teacher should be able to create a pleasant atmosphere in the teaching learning process. In learning English teachers are required to adapt to technology so that learning is more attractive to students’ interest in learning. One way to create a fun learning atmosphere in learning English is by developing a video learning through the Canva application. Canva is an application that can be used in the process of creating learning media. However, there are still many teachers who are unable to operate various features of technology especially Canva. This study aimed to display an information about the advantage of Canva application in learning English. This study used a qualitative method with the library research approach to collect the data. The data were taken from two previous studies which investigating the benefit of Canva Application. The result of the study shows that Canva Application contributes in a positive way in helping to create English Language Learning materials. It is expected that English teachers to be able to develop video-based learning media because it greatly helps the clarity of the material and attracts interest for students in learning English